(untitled) (Journal of Scientific Research, 2025)
In this study, the main goal is to improve power quality (PQ) in radial distribution systems (RDS) by carefully integrating active filters (AFs). Nonlinear loads (NLs) can produce harmonics that negatively affect PQ. The effective mitigation of NL harmonics by introducing AFs lowers the total harmonic distortion in voltage (THDv). Simulations using the IEEE-69 bus system validate the effectiveness of this method by showing a notable improvement in PQ together with minimum AF sizing. In this work, two optimization techniques are compared to get the lowest AF current: ant lion optimizer (ALO), and improved particle swarm optimization (IPSO). The simulation results show a notable improvement in PQ and validate the efficacy of the suggested AF placement and sizing technique. The optimization procedure shows that ALO minimizes AF current more effectively than IPSO. Finding the best approach to improve the location and size of AFs is made easier with the help of this comparative analysis of optimization techniques.